Sequential VEGF and BMP-2 releasing PLA-PEG-PLA scaffolds for bone tissue engineering: I. Design and in vitro tests. (17th February 2017) - Eğri, Sinan; Eczacıoğlu, Numan
Abstract: Biodegradable PLA-PEG-PLA block copolymers were synthesized with desired backbone structures and molecular weights using PEG20000. Rectangular scaffolds were prepared by freeze drying with or without using NaCl particles. Bone morphogenetic protein (BMP)-2 was loaded to the matrix after the scaffold formation for sustained release while vascular endothelial growth factor (VEGF) was loaded within the pores with gelatin solution. VEGF release was quite fast and almost 60% of it was released in 2 d. However, sequential – sustained released was observed for BMP-2 in the following few months. Corporation of VEGF/BMP-2 couple into the scaffolds increased the cell adhesion and proliferation. Neither significant cytotoxicity nor apoptosis/necrosis were observed.